HISTOPATHOLOGICAL SPECTRUM OF SKIN LESIONS IN CENTRAL INDIA: INSIGHTS FROM A TERTIARY CARE CENTER - Dr. Pooja Gulhane, Dr. Arunima Cladius, Dr. Rajendra Kumar Chandrakar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Skin lesions represent a diverse group of conditions ranging from non-neoplastic toneoplastic disorders. Due to overlapping clinical features, histopathological examination isessential for accurate diagnosis.